Faktor Faktor yang Mempengaruhi Penyusunan Laporan Keuangan UMKM Berdasarkan SAK Indonesia untuk EMKM - Deasy Rahmayanti; Ferdawati; Ria Angriani (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the influence of perceptions of education level, perceptions of accounting understanding, socialization of SAK Indonesia for EMKM, and perceptions of business scale on the preparation of financial reports for Micro, Small, and Medium Enterprises (UMKM) based on SAK Indonesia for EMKM in Lubuk Kilangan District, Padang City. Data was collected through questionnaires distributed to 100 UMKM actors in the culinary sector. The analysis technique used is Structural Equation Modeling Partial Least Squares (SEM-PLS). The results show that perceptions of education level, perceptions of accounting understanding, socialization of SAK Indonesia for EMKM, and perceptions of business scale positively affect the preparation of financial reports based on SAK Indonesia for EMKM. This study contributes to increasing UMKM's understanding of the importance of preparing financial reports according to standards, as well as to government policy development in supporting the implementation of SAK Indonesia for EMKM in the UMKM sector.